The legitimacy of the discursive principle and its interlacing with the argumentation of fundamental rights. An analysis based on the habermasian theory - Durango Álvarez, Gerardo A. (2008)
The main interest of this article is to analyze the proposal of foundation of the fundamental rights sketched by Habermas starting over the theory of the communicative action, of the deliberative democracy and of the reconstruction of the modern right that this author proposes from the beginning of discursive and the discursive paradigm of the law. Consequently, pretend to explore the connection among fundamental rights, formal and informal public spaces of participation and a deliberalive model of deliberative constitutional democracy that Habermas settles from several suppositions and elements that articulate its theory of the communicative action and, in a more precise way, its discursive principle as search and founding, as much of right as communicative-normative  spaces.